Peran Orang Tua dan Sumber Informasi dalam Pendidikan Seks dengan Perilaku Seksual Remaja pada Masa Pubertas di SMAN 1 Turi - Sujarwati Sujarwati; Anafrin Yugistyowati; Kayat Haryani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Adolescent is transition period or transition from childhood to adulthood. Based on the baseline study, showed that from 268 students about 66 (60%) male students said that they ever doing masturbation and 5 (1.75%) students who take counseling had ever sexual intercourse and in the academic year 2012/2013 there was 1 (0.35%) student was pregnant before marriage. The purpose of this research was to observe role of parents and information resources relationship in sex education with sexual behavior adolescents in puberty at SMAN 1 Turi. Study design was inductive with cross sectional. The samples were adolescents aged 16-19 years. The sampling technique was done by purposive sampling resulted on 73 respondents. The analysis used Multiple Regression and Partial Correlation Test. The results showed that 50 (68.5%) students with role of parents was good, information resources 38 (52.1%) students and sexual behavior of adolescent 53 (72.6%) students was good. Multivariate analysis showed that there was the relationship between role of parent and information resources with sexual behavior period in puberty at SMAN 1 Turi with p=0.000 (p<0.05). In conclusion, there was relationship between role of parents and information resources in sex education with sexual behavior of adolescent in puberty at SMAN 1 Turi.